Visualizing large hierarchies with Drawer Trees - Yalong Yang; Ning Dou; Shuai Zhao; Zhichao Yang; Kang Zhang; Quang Vinh Nguyen (SAC'14: Proceedings of the ACM Symposium on Applied Computing, 2014)
Enclosure partitioning approaches, such as Treemaps, have proved their effectiveness in visualizing large hierarchical structures within a compact and limited display area. Most of the Treemaps techniques do not use node-links to show the structural relations. This paper presents a new tree visualization approach known as Drawer-Tree that can be used to present the structure, organization and interrelation of big data. By utilizing the display space with traditional node-link visualization, we have developed a novel method for visualizing tree structures with high scalability. The name "drawer" is a metaphor that helps people understand the visualization.